Моллюски подотряда Ellobioidei (Pulmonata) побережья Средиземного моря и Европейской Атлантики - Старобогатов, Я.И.; Анистратенко, В.В. (Вестник зоологии, 1993)
A revision of the families Leucophytiidae and Cassidulidae. First of them is represented in the region by the genus Leucophytia with 4 species, second — by genera Pseudornelampus (4 species), Volateta gen. n. (3 species, incl. type Volula dendculata Mtg.), Ovatella (2 species) and Myosolella (5 species). 4 Myosolella species and 1 Ouatella are recorded for Black Sea shores.